Feminist Auto/biography as a Means of Empowering Women: A Case Study of Sylvia Plath’s The Bell Jar and Janet Frame’s Faces in the Water - Fisiak, Tomasz (Text Matters: A Journal of Literature, Theory and Culture, 2011)
Feminism, as a political, social and cultural movement, pays much attention to the importance of text. Text is the carrier of important thoughts, truths, ideas. It becomes a means of empowering women, a support in their fight for free expression, equality, intellectual emancipation. By "text" one should understand not only official documents, manifestos or articles. The term also refers to a wide range of literary products—poetry, novels, diaries. The language of literature enables female authors to omit obstacles and constraints imposed by the phallogocentric world, a world dominated by masculine propaganda. Through writing, female authors have an opportunity to liberate their creative potential and regain the territory for unlimited expression. In order to produce a truly powerful text, they resort to a variety of writing styles and techniques. Here the notions of a situated knowledge and context sensitivity prove useful. There are three methodologies working within situated knowledge, namely, the politics of location, self-reflexivity and feminist auto/biography. All of them regard text as a fundamental tool to signify one's authority, yet feminist auto/biography, a concept widely discussed by the British theorist Liz Stanley, appears to be the most empowering mode of writing. It challenges the overused genre of auto/biography and reconstructs its role within feminist epistemologies, thus creating a favourable environment for text production. The works by Sylvia Plath and Janet Frame can be analyzed from the point of view of auto/biographical empowerment, even though their auto/biographical potential is mainly instinctive. Nevertheless, they help to comprehend the strength of the auto/biographical. The aim of this article is to "investigate" two novels by these authors, The Bell Jar by Sylvia Plath and Faces in the Water by Janet Frame, and their compatibility with Stanley's concept. The paper attempts to answer several questions. Are these novels actual feminist auto/biographies or rather fictional auto/biographies with feminist undertones? What kind of narrative strategy is used to achieve the effect of authority over the text? Last but not least, what is the function of auto/biographical narration in the case of these two novels? The article also explores the idea of writing as a means of regaining control over one's life (with references to the authors' biographies and parallels between their lives and lives of their fictive alter egos).